1988
DOI: 10.1126/science.3194758
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Cattle Against Rinderpest with Vaccinia Virus Recombinants Expressing the HA or F Gene

Abstract: Rinderpest is a highly contagious ruminant viral disease manifested by a rapid course and greater than 90% mortality. Infectious vaccinia virus recombinants were constructed that express either the hemagglutinin or the fusion gene of rinderpest virus. All cattle vaccinated with either recombinant or with the combined recombinants produced neutralizing antibodies against rinderpest virus and were protected against the disease when challenged with more than 1000 times the lethal dose of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 17 publications
2
62
0
Order By: Relevance
“…Although the F protein can be the target of neutralizing antibodies (13), most of the protective immunity to MV is directed against the H protein (4). Similarly, the neutralizing antibodies have been induced with much higher titers in cattle by immunization with vaccinia virus recombinant encoding the H protein of RPV (RPV-H) than with that encoding the F protein (21). The B-cell epitopes on the H protein of MV (MV-H) have been analyzed by several groups by using monoclonal antibodies (MAbs) and synthetic peptides.…”
mentioning
confidence: 99%
“…Although the F protein can be the target of neutralizing antibodies (13), most of the protective immunity to MV is directed against the H protein (4). Similarly, the neutralizing antibodies have been induced with much higher titers in cattle by immunization with vaccinia virus recombinant encoding the H protein of RPV (RPV-H) than with that encoding the F protein (21). The B-cell epitopes on the H protein of MV (MV-H) have been analyzed by several groups by using monoclonal antibodies (MAbs) and synthetic peptides.…”
mentioning
confidence: 99%
“…Recombinant vaccinia viruses have been widely assessed for use as vaccine vectors in several species and have been shown to give rise to protective cytotoxic T cell responses (9). Indeed, a recent report has shown that recombinant vaccinia viruses incorporating the fusion protein or haemagglutinin genes of rinderpest virus induce serum neutralising antibody titres which protect cattle against challenge with the virus (82). Successful use of herpes viruses and adenoviruses as antigen delivery vehicles has also been reported in some species (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, only two have been used in large-scale field trials. One is a recombinant rinderpest vaccine which has been tested in Africa and India [14]. The other is the recombinant rabies vaccine used for oral immunization of wild foxes, the major reservoir of rabies in Western Europe.…”
Section: Poxvirus Recombinant Vaccinesmentioning
confidence: 99%